An analytical observational study on the prognostic implication of postoperative serial serum lactate level for complications and predicting length of intensive therapy unit stay after major abdominal surgery - Mondal, Moumita; Santra, Sankari; Choudhuri, Rajat; Das, Amartya (International Journal of Research in Medical Sciences, 2021)
Background: Post-operative microcirculatory alteration causes hypoperfusion, tissue hypoxia and organ dysfunction, resulting in significant morbidity and mortality. Increase in serum lactate level in response to tissue hypoxia may serve as a cost effective tool to assess status of all organ dysfunction being sensitive but not organ specific and may help in early prognostication. Aim of this study was to investigate the association of blood lactate levels during the first 24 hours after surgery with postoperative morbidity and mortality, with length of ITU stay and to correlate the lactate values at various time points with different postoperative complications (POC). Methods: 150 patients undergoing elective abdominal surgery were included. Blood lactate (mmol/lit) levels were measured immediately on admission to the Intensive Therapy Unit (ITU) and at 6, 12, and 24 hours of admission. The parameters of clinical outcome included were mortality, shock, Acute kidney injury (AKI), respiratory failure, wound dehiscence and length of ITU stay. Heart Rate, Mean Arterial Pressure, spo2, Temperature and Urine output were also measured. Results: There was statistically significant difference in the lactate levels measured at the above mentioned point of time (0, 6, 12 and 24h) in cases with death and without fatal outcome, with and without respiratory failure, with and without AKI, with and without shock and in cases with and without wound dehiscence (p<0.05). There was a statistically significant difference in urine output, duration of ITU stay and duration of intubation (p<0.05). Conclusions: Increased serum lactate levels were significantly associated with postoperative complications, mortality and length of ITU stay in patients undergoing major elective abdominal surgery.